"Incurable Megalomania" and "Fantasies of Expansion": The German Army Reimagines Empire in Occupied Poland, 1915–1918. Issue 4 (December 2021) - Kettler, Mark T.
Abstract: Plans for a Polish "border strip" are frequently cited to argue that the German army entered the First World War committed to pacifying conquered space through Germanization. This article contends that, in 1914, the German officer corps did not understand national homogeneity as essential for imperial security. Many influential officers insisted that Polish identity was compatible with German imperial loyalty. They supported a multinational imperial model, proposing to trade Poland its cultural and political autonomy for the acceptance of German suzerainty in foreign policy and military command. The army's preference for Germanizing space developed during the occupation of Russian Poland, as officers learned to conflate diversity with imperial fragility. Only a series of political crises after 1916 shifted military opinion against multinational imperialism. Increasingly convinced that Poland would betray the German Empire, some officers abandoned multinationalism. Others revised their plans to contain Poland and fortify Germany by annexing and Germanizing Polish space.